PERAN MANAJER DALAM PENANGGULANGAN KONFLIK ORGANISASI - Dhorifin, Muhammad (J-MPI (Jurnal Manajemen Pendidikan Islam), 2016)
The main objective of conflict management behavior is to establish and maintain cooperative working relationship with subordinates, peers, superiors and outsiders. Some forms of conflict management behaviors such as bargaining and integrative problem solving, the approaches to dealing with conflicts involving a manager and others whose assistance they need to achieve work goals. Conflict management as well as efforts to mediate conflicts among others. The main purpose of behavior to build a team is to build a working unit in solidarity with the identification of a strong and a high level of cooperation.